1996
DOI: 10.1021/bi960406h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Cross-Linking of Rabbit Skeletal Troponin I Deletion Mutants with Troponin C and Its Thiol Mutants:  The Inhibitory Region Enhances Binding of Troponin I Fragments to Troponin C

Abstract: Contraction of vertebrate striated muscle is regulated by the strong Ca(2+)-dependent interaction between troponin I (TnI) and troponin C (TnC). To critically evaluate this interaction, we generated four recombinant deletion fragments of rabbit fast skeletal TnI: the NH2-terminal fragment (TnI1-94), the NH2 terminus and the inhibitory region (TnI1-120), the inhibitory region and the COOH terminus (TnI96-181), and the COOH-terminal fragment (TnI122-181) containing amino acid residues 1-94, 1-120, 96-181, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Those results complement the results of Farah et al (10) showing that the inhibitory region is involved in the Ca 2ϩ -dependent binding to TnC and that TnI binds TnC in an antiparallel manner: the C-terminal region (regulatory) of TnI interacts with the N terminus (regulatory) of TnC, the C-terminal region (structural) of TnC interacts with the N terminus (structural) of TnI, and the inhibitory region of TnI interacts with both the N-and Cterminal regions of TnC. Support to this model was also given by Sheng et al (15) and by Jha et al (16). McKay et al (19), using a peptide corresponding to residues 115-131 of TnI, showed that this region binds to the hydrophobic pocket of N-domain of TnC (36).…”
Section: The Region Between the Inhibitory Region And Residue 147 Of mentioning
confidence: 54%
See 1 more Smart Citation
“…Those results complement the results of Farah et al (10) showing that the inhibitory region is involved in the Ca 2ϩ -dependent binding to TnC and that TnI binds TnC in an antiparallel manner: the C-terminal region (regulatory) of TnI interacts with the N terminus (regulatory) of TnC, the C-terminal region (structural) of TnC interacts with the N terminus (structural) of TnI, and the inhibitory region of TnI interacts with both the N-and Cterminal regions of TnC. Support to this model was also given by Sheng et al (15) and by Jha et al (16). McKay et al (19), using a peptide corresponding to residues 115-131 of TnI, showed that this region binds to the hydrophobic pocket of N-domain of TnC (36).…”
Section: The Region Between the Inhibitory Region And Residue 147 Of mentioning
confidence: 54%
“…At this time, little is known about the TnI structure, even though information from low resolution structures is available (12,13) and part of its N-terminal region of TnI (residues 1-47) has been crystallized in a complex with TnC (14). However, the use of deletion mutants (10,15,16) and peptides (11,(17)(18)(19) containing regions of TnI has been shown to be a powerful tool for studying the functions of different regions of this protein and for connecting the functions of TnI with its primary structure.…”
mentioning
confidence: 99%
“…However, it was not known exactly which residues of TnI bind to TnC nor where this complex occurs on TnC. Mutation studies (23), cross-linking experiments (17,18,22,24,27), and low angle x-ray diffraction structures (15) have suggested that the exposed TnC hydrophobic pockets are the site of TnC⅐TnI interaction. Interestingly the TnC⅐TnI complex formation was insensitive to calcium unless tropomyosin and other members of the troponin complex were present, although calcium was found to stabilize the isolated TnC⅐TnI complex (6,28).…”
mentioning
confidence: 99%
“…Troponin C (TnC), a member of the EF-hand family of proteins, binds Ca 2ϩ , and relieves TnI inhibition of actin-myosin interaction (see ref. 4 and references therein). Troponin T (TnT) is a structural link between the Tn complex and tropomyosin, and it also increases the cooperativity of actin-tropomyosin binding to myosin (5).…”
mentioning
confidence: 99%